2013
DOI: 10.5194/se-4-135-2013
|View full text |Cite
|
Sign up to set email alerts
|

Strain localisation in mechanically layered rocks beneath detachment zones: insights from numerical modelling

Abstract: Abstract.We have designed a series of fully dynamic numerical simulations aimed at assessing how the orientation of mechanical layering in rocks controls the orientation of shear bands and the depth of penetration of strain in the footwall of detachment zones. Two parametric studies are presented.In the first one, the influence of stratification orientation on the occurrence and mode of strain localisation is tested by varying initial dip of inherited layering in the footwall with regard to the orientation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Details of the 2D version of the code are given in Appendix A, as well as in Jourdon et al (2018) and Ioannidi et al (2021). We consider the structures observed in the field to be scale independent, as suggested by recent studies (Fagereng, 2011;Grigull et al, 2012;Ioannidi et al, 2021;Le Pourhiet et al, 2013), therefore we upscale field outcrop scales to map scales (from a cm-scale to a m-scale). For more details, see Discussion on scaling (Section 5.1.1).…”
Section: Numerical Models Of Stress Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the 2D version of the code are given in Appendix A, as well as in Jourdon et al (2018) and Ioannidi et al (2021). We consider the structures observed in the field to be scale independent, as suggested by recent studies (Fagereng, 2011;Grigull et al, 2012;Ioannidi et al, 2021;Le Pourhiet et al, 2013), therefore we upscale field outcrop scales to map scales (from a cm-scale to a m-scale). For more details, see Discussion on scaling (Section 5.1.1).…”
Section: Numerical Models Of Stress Distributionmentioning
confidence: 99%
“…Previous work (Fagereng, 2011;Grigull et al, 2012;Ioannidi et al, 2021;Le Pourhiet et al, 2013) showed that the dimensions of blocks/structures do not affect the results of a model, as long as block distribution, strain rate and deformation mechanisms are the same at the different scales. Here, we created a numerical map representing the average block distribution of the field observations (7%).…”
Section: Scalingmentioning
confidence: 99%
“…Experimentally derived flow laws characterizing the rheology of single mineral phases often exhibit a power law behavior. Modeling the deformation of heterogenous power law viscous materials allows to unravel the dynamics of shear localization and the formation of rock fabrics [Mancktelow, 2002;Jessell et al, 2009;Deubelbeiss et al, 2011;Dabrowski et al, 2012;Le Pourhiet et al, 2013]. We have set up a power law model consisting in randomly located highly viscous elliptical inclusions.…”
Section: Deformation Of Heterogenous Power Law Viscous Materialsmentioning
confidence: 99%
“…It is clear that continental break-up can only be achieved if there is localization of deformation (Le Pourhiet et al, 2013;Moresi et al, 2007;Regenauer-Lieb et al, 2008). This is achieved by feedback and possibly the presence of magma (Corti et al, 2003).…”
Section: Break-up Mechanicsmentioning
confidence: 99%